2016
DOI: 10.1053/j.gastro.2015.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Response to Etrolizumab and Expression of Integrin αE and Granzyme A in Colon Biopsies of Patients With Ulcerative Colitis

Abstract: Levels of GZMA and ITGAE mRNAs in colon tissues can identify patients with UC who are most likely to benefit from etrolizumab; expression levels decrease with etrolizumab administration in biomarker(high) patients. Larger, prospective studies of markers are needed to assess their clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 36 publications
2
96
0
Order By: Relevance
“…Thus, it is very likely that αEβ7 + T cells communicate with the epithelium. Independent reports have recently shown that αEβ7 is enriched in pro-inflammatory T cell subsets (22, 35) and that αEβ7 + T cells express higher levels of granzyme A than αEβ7 − T cells (36). In vivo , this might result in deleterious effects of such αEβ7-expressing on epithelial cells, which is supported by some of our data showing correlations of changes in αEβ7 integrin with changes in clinical parameters that are indicative of intestinal epithelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is very likely that αEβ7 + T cells communicate with the epithelium. Independent reports have recently shown that αEβ7 is enriched in pro-inflammatory T cell subsets (22, 35) and that αEβ7 + T cells express higher levels of granzyme A than αEβ7 − T cells (36). In vivo , this might result in deleterious effects of such αEβ7-expressing on epithelial cells, which is supported by some of our data showing correlations of changes in αEβ7 integrin with changes in clinical parameters that are indicative of intestinal epithelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…These results are concordant with similar observations of lesser efficacy of vedolizumab among those with prior anti-TNF treatment. Additional analyses suggest that response to etrolizumab is associated with higher baseline gene expression of αE and with higher numbers of αE-expressing cells on colonic biopsy [31] . This finding, consistent with the anticipated mechanism of action, suggests that this agent may be more effectively targeted to specific subpopulations of patients to increase the likelihood of treatment success.…”
Section: Etrolizumabmentioning
confidence: 95%
“…Completed phase 1 and 2 and ongoing phase 3 clinical trials have shown that blockade of αEβ7 with etrolizumab is well tolerated, with rates of serious adverse events similar to those with placebo . In addition, both CD4 + αEβ7 + and CD8 + αEβ7 + cells are pro‐inflammatory in phenotype; CD4 + αEβ7 + demonstrating fewer markers associated with T reg cells including FoxP3 relative to CD4 + αEβ7 − lymphocytes …”
Section: Safety Of Anti‐integrin Therapiesmentioning
confidence: 99%